Analysis of Theme, Setting, Characters, and Message in the Novel Sunyi Paling Riuh by Fajar Sulaiman - Yuliana Iswanty; Suhardi; Tessa Dwi Leoni; Isnaini Leo Shanty; Legi Elfitra (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This study discusses the analysis of intrinsic elements including theme, setting, characters, and message in the novel Sunyi Paling Riuh by Fajar Sulaiman. Intrinsic elements are important parts of a fictional work, consisting of the fundamental components of the story. The aim of this research is to describe the themes, settings, characters, and messages contained in the novel Sunyi Paling Riuh. This research employs a qualitative descriptive method, with data collection techniques consisting of reading, observing, and note-taking. The main instrument in this study is the researcher herself, assisted by a data inventory table. The results of the study show that the analyzed intrinsic elements include: (1) The themes raised in the novel are about loss, loneliness, love, family, and acceptance; (2) The settings include places such as home, school, café, red room, and the city of Jakarta; the times include morning, afternoon, and night; (3) The main character, Dhuha, is portrayed as introspective and full of inner conflict, while supporting characters such as Zoya, Saba, and Bapak strengthen the plot; (4) The messages conveyed in the novel consist of both explicit and implicit messages. These include messages about the importance of sincerely accepting loss, having the courage to face reality, self-love, the importance of support from close ones, and the need to learn to let go, forgive, and continue to hope in life. Out of 41 analyzed messages, 23 were conveyed implicitly, while the remaining 16 were conveyed explicitly.